Indication and complication of caesarean section at tertiary care hospital: a retrospective study - Ur Rehman, Bilal; Gul, Hiba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The incidence of cesarean section is steadily rising. Cesarean delivery has played a major role in lowering both maternal and perinatal morbidity and mortality rates. There are various factors involved in the rise of rate of cesarean section like rising incidence of primary cesarean delivery, identification of high-risk pregnancy, wider use of repeat cesarean section, rising rates of induction of labor and failure of induction, no reassuring fetal status etc. Methods: A retrospective cross-sectional study was conducted. Data was collected from patient records of the hospital during 1st January 2018 to 30th June 2018. All patients (N= 602) who had delivered their baby by caesarean section were included in the study. Data were analyzed by help of SPSS version 21 after proper compilation. Results: Among all women who underwent cesarean section, majority were age group between 21 and 30 years (67.1%). Repeat cesarean section (48.5%), followed by fetal distress (18.9%), oligohydramnias (6.6%) and cephalopelvic disproportion (6.5%) were most common among all major indication of cesarean section. Intrapartum complication (2.0%) includes postpartum hemorrhage (1.2%), CS hysterectomy (0.5%), bladder injury (0.3%) and postpartum complication (2.3%) including UTI (0.8), wound infection (0.5%), sepsis (0.5%), lactation failure (0.5%) were major maternal complication of cesarean section. Conclusions: Reduction of number of primary cesarean section, successful VBAC, individualization of the indication and careful evaluation, following standardized guidelines can help to keep rate of cesarean section to the possible minimum level.